2021
DOI: 10.1002/advs.202103608
|View full text |Cite
|
Sign up to set email alerts
|

Mesopore Controls the Responses of Blood Clot‐Immune Complex via Modulating Fibrin Network

Abstract: Formation of blood clots, particularly the fibrin network and fibrin network‐mediated early inflammatory responses, plays a critical role in determining the eventual tissue repair or regeneration following an injury. Owing to the potential role of fibrin network in mediating clot‐immune responses, it is of great importance to determine whether clot‐immune responses can be regulated via modulating the parameters of fibrin network. Since the diameter of D‐terminal of a fibrinogen molecule is 9 nm, four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Raw data of FASTQ format was generated, further being calculated into read counts and TPM data for downstream analysis. Bioinformatic analysis of transcriptome data was conducted using R studio 4.0 (The R Foundation, USA) and Cytoscape 3.8 (The Cytoscape Consortium, USA) software as previously described [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Raw data of FASTQ format was generated, further being calculated into read counts and TPM data for downstream analysis. Bioinformatic analysis of transcriptome data was conducted using R studio 4.0 (The R Foundation, USA) and Cytoscape 3.8 (The Cytoscape Consortium, USA) software as previously described [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ta-MBGs used in the present study possess nanopores of about 4 nm [ 52 ] and probably were accessible to fibrinogen. Another study [ 58 ] explored the effect of mesopore size on the fibrinogen adsorption and hence the fibrin network formation. Considering fibrinogen’s dimensions: length of 47.5 nm (E domain) and diameter of 6 × 9 nm (D domain), they tested the effect of various mesopore sizes (2, 8, 14, and 20 nm) on the fibrinogen adsorption to analyze linear growth of fibrinogen’s D domain in clot formation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 58 ] explored the effect of mesopore size on the fibrinogen adsorption and hence the fibrin network formation. Considering fibrinogen’s dimensions: length of 47.5 nm (E domain) and diameter of 6 × 9 nm (D domain), they tested the effect of various mesopore sizes (2, 8, 14, and 20 nm) on the fibrinogen adsorption to analyze linear growth of fibrinogen’s D domain in clot formation [ 58 ]. Their study concluded that the pore sizes more than 9 nm (D domain dimension), i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations